Effect of Insecticides Imidacloprid and Alpha-Cypermethrin on the Development of Pea (Pisum sativum L.) Nodules - Artemii P. Gorshkov; Pyotr G. Kusakin; Maxim G. Vorobiev; Anna V. Tsyganova; Viktor E. Tsyganov (Plants)
Insecticides are used commonly in agricultural production to defend plants, including legumes, from insect pests. It is a known fact that insecticides can have a harmful effect on the legume–rhizobial symbiosis. In this study, the effects of systemic seed treatment insecticide Imidor Pro (imidacloprid) and foliar insecticide Faskord (alpha-cypermethrin) on the structural organization of pea (Pisum sativum L.) nodules and their transcriptomic activity were investigated. The plants were treated as recommended by the manufacturer (10 mg/mL for Imidor Pro and 50 µg/mL for Faskord) and twofold concentrations were used for both insecticides. Insecticides had no visible effect on the growth of pea plants. The nodules also showed no visible changes, except for the variant treated with twofold concentration of Imidor Pro. However, the dry weight of shoots and roots differed significantly in insecticide-treated plants compared to untreated plants in almost all treatments. The number of nodules decreased in variants with Imidor Pro treatment. At the ultrastructural level, both insecticides caused cell wall deformation, poly-β-hydroxybutyrate accumulation in bacteroids, expansion of the peribacteroid space in symbiosomes, and inclusions in vacuoles. Treatment with Faskord caused chromatin condensation in nucleus. Imidor Pro treatment caused hypertrophy of infection droplets by increasing the amount of matrix, as confirmed by immunofluorescence analysis of extensins. Transcriptome analysis revealed upregulation of expression of a number of extensin-like protein-coding genes in nodules after the Imidor Pro treatment. Overall, both insecticides caused some minor changes in the legume–rhizobial system when used at recommended doses, but Faskord, an enteric contact insecticide, has fewer negative effects on symbiotic nodules and legume plants; of these two insecticides, it is preferred in pea agricultural production.